PENGARUH PERPUTARAN MODAL KERJA DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS - Ahmat Widianto; Herman Sjahruddin; Mappamiring P; Didit Fachri Rifai (LP2M Universitas Bina Bangsa, 2024)
This study aims to test and analyze the effect of working capital turnover and inventory turnover on profitability in automotive companies listed on the Indonesia Stock Exchange. The type of data used is secondary data obtained from annual reports for the 2020-2022 period of automotive companies listed on the Indonesia Stock Exchange. The sampling method used was purposive sampling. After selecting samples based on certain criteria, 13 samples were obtained, resulting in 39 analytical data. The data analysis method uses Common Effect Model (CEM) panel data regression analysis with Eviews 12. The research results show that working capital turnover has a significant positive effect on profitability and inventory turnover has an insignificant positive effect on profitability in automotive companies listed on the Indonesia Stock Exchange